Physiology of exercise and healthy aging - Taylor, Albert W.
"This text is written explicitly for readers with an interest in the aging process and the effects that exercise has on the quality of life and various diseases and maladies of the aging population. It is expected that the readers using this book as a course textbook or as auxiliary reading for a course, will have taken at least an introductory course in human physiology. The text refers throughout to the three groups in the aging and health spectrum, average aging individuals, the frail elderly and Masters Athletes"
Preceded by Physiology of exercise and healthy aging / Albert W. Taylor, Michel J. Johnson. c2008.
MS Salazar (Recommending faculty) AY2022-2023
Includes bibliographical references and index.
Keywords: Healthy Aging -- physiology; Exercise -- physiology; Aging -- physiology